MESHING PERFORMANCE ANALYSIS OF TAPERED ROLLER ENVELOPING END FACE MESHING WORM DRIVE (MT) - WEN YuJie; LIAO HongHui; LIU ZaiXin; LI LingYu (Jixie qiangdu)
The end face meshing worm drive with tapered roller envelope has many simultaneous meshing tooth pairs and can eliminate clearance. According to the gear meshing principle and differential geometry principle, the meshing mathematical model of the transmission pair is established, the worm tooth surface equation and meshing function are deduced, and the meshing performance calculation formula is obtained. Matlab software is used to analyze the effects of small end radius, throat diameter coefficient and half cone angle of cone on the meshing performance evaluation parameters of the transmission pair induced normal curvature, lubrication angle, relative entrainment speed and self rotation angle. The analysis results show that the transmission pair has good meshing performance.